Intuitionistic Fuzzy Capital Budgeting Problem Using Non-Linear Programming: Wallbox Fast Charging OEM Application - Haktanir, Elif (OLD CITY PUBLISHING INC, 2023)
Capital budgeting is the selection of independent investment alternatives to maximize profits under a certain budget constraint. Initial investment cost, annual cash flows, interest rate and budget limit are investment parameters that involve uncertainty in real life. These parameters can be defined as a range, and their memberships and non-memberships to a fuzzy set can be specified. In this article, the capital budgeting problem is modeled as a 0-1 non-linear programming problem using intuitionistic fuzzy set theory. The validation of the model is demonstrated with a Wall -box Fast Charging OEM application problem. The sensitivities of the model parameters on the decision were also examined.
Keywords: Intuitionistic fuzzy sets; capital budgeting; non-linear programming; independent projects; present worth; MULTIATTRIBUTE DECISION-MAKING; OPTIMIZATION; METHODOLOGY; Computer Science; Science & Technology - Other Topics